Requirements Engineering for Integrated Social Assistance Distribution Information Systems Using a Microservices Architecture Approach - Angelini, Siski; Bangkalang, Dwi Hosanna (Sistemasi: Jurnal Sistem Informasi, 2024)
Distribution of social aid on target is important to help the welfare of people in need. In Bugel Subdistrict, Salatiga, this distribution has several problems, namely, data discrepancies, the application process is not transparent, and there is no distribution monitoring, resulting in social assistance recipients not being on target and affecting decisions on providing assistance for the next period. Therefore, a social assistance distribution information system is needed to assist in managing integrated data collection and monitoring distribution and application status. The information system requirements engineering method uses the system engineering life cycle method developed by Alexander Kossiakoff with a focus on the concept development stage. This research aims to identify the initial needs for a data management information system for social assistance recipients by producing a distribution of coordinate points as well as new distribution and submission monitoring features using a microservices architecture approach and visualizing with a design display using mobile first design technology referring to a responsive mobile display, containing detailed information, images , location routes to improve the performance of social assistance administrators with real-time data access